ASSOCIATION OF OVERCONFIDENCE MANAGEMENT WITH EARNINGS MANAGEMENT: MODERATION OF AUDIT COMMITTEE EFFECTIVENESS - Islamudin, Ardhi (JEA17: Jurnal Ekonomi Akuntansi, 2022)
This study aims to obtain information and empirical evidence about the association of managerial overconfidence on earnings management and the effect of moderating the effectiveness of the audit committee. This study uses 1938 observations of companies listed on the Indonesian stock exchange for six periods from 2013 to 2018. The analysis technique used in this study is a moderated regression analysis using SPSS 25 software. This study finds that managerial overconfidence has a significant positive association. on earnings management, this is due to managerial overconfidence who feels he is better than other parties so that they ignore the realistic evaluation, when an investment project is not as estimated, they will perform earnings management to cover their miscalculations. Furthermore, the audit committee was unable to reduce the positive association of managerial overconfidence on earnings management, from the research data it was found that the company only met a few criteria for the effectiveness of the audit committee. Keywords: Managerial, Overconfidence, Earnings Management, Good Corporate Governance, Audit Committee